Family Planning and Reproductive Health - Amarin, Zouhair; Abduljabbar, Hassan (IntechOpen, 2020)
Female reproductive topics are very common and can affect the patient's quality of life. Such topics include puberty, endometriosis, breastfeeding, subfertility, menstrual problems, polycystic ovary syndrome, problems during pregnancy, uterine fibroids, various benign and malignant conditions of the reproductive organs, various sexually transmitted infections, family planning, and contraception. Good reproductive health covers the physical, mental, and social well-being. However, to maintain it, women need to be informed and empowered to protect themselves through access to services that can help them have a fit pregnancy, safe delivery, and healthy baby. This book is intended to cover some of the female reproductive issues for all specialties involved in health care for women.